Performance of Xpert MTB/RIF by Using Gastric Lavage Samplein The Diagnosis of Pulmonary Tuberculosis in HIV Patients withSuspected Pulmonary Tuberculosis - Mboeik, Manuel Lamberto Willem; Pitoyo, Ceva Wicaksono; Karjadi, Teguh Harjono; Karuniawati, Anis; Dewiasty, Esthika (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Xpert MTB/RIF test on gastric lavage sample may improve pulmonary tuberculosis (TB) case finding, but its performance as a diagnostic test for pulmonary TB in HIV-infected adults patients has not been studied widely, including in Indonesia. This study aims to determine the performance of the Xpert MTB/RIF test in diagnosing pulmonary tuberculosis 30 | Jurnal Penyakit Dalam Indonesia | Vol. 5, No. 1 | Maret 2018 Manuel Lamberto Willem Mboeik, Ceva Wicaksono Pitoyo, Teguh Harjono Karjadi, Anis Karuniawati, Esthika Dewiasty among HIV-infected adult patients with suspected pulmonary tuberculosis by using gastric lavage sample. Method. A cross-sectional study was conducted on adult HIV-infected patients with suspected pulmonary tuberculosis in Cipto Mangunkusumo hospital Jakarta between February 2016 and June 2017. Gastric lavage sample and sputum sample collection were performed for Xpert MTB/RIF test and acif fast bacilli (AFB) smear examination. Results. Among total of 117 subjects, 81 (69,2%) subjects were unable to expectorate sputum. M tuberculosis was detected on Xpert MTB/RIF using gastric lavage samples in 34 (29,1%) subjects, AFB in 4 of 36 sputum samples and 2 of 117 gastric lavage samples. The drug sensitivity test on all 34 Xpert MTB/RIF positive subjects showed no rifampicin resistance. Fifty-one (43.6%) subjects were diagnosed as clinical pulmonary tuberculosis, 26 subjects among them were positive on Xpert MTB/ RIF assay, 4 subjects were smear sputum positive and 1 subject was gastric lavage smear positive. Using clinical diagnosis of pulmonary TB as gold standard, a single Xpert MTB/RIF assay using gastric lavage sample showed sensitivity of 50.98% (95% CI: 36.6-65.25), specificity 87.88% (95% CI: 77,1-94,62), positive predictive value 76,47% (95%CI: 61,67-86,78) and negative predictive value 69,88% (95% CI: 63,36-75.68). Conclusion. Xpert MTB/RIF performed on gastric lavage samples showed sensitivity of 50.98% and specificity 87.88% in clinical diagnosis of pulmonary tuberculosis in HIV-positive patients with pulmonary tuberculosis.